2008
DOI: 10.1590/s0102-311x2008000200021
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação transcultural do Female Sexual Function Index

Abstract: IntroduçãoNo século XX, o comportamento sexual tornouse objeto de estudo empírico, afastando-se da classificação nosológica médica de crimes e perversões sexuais que abundaram no século anterior. Um desses marcos são os estudos de Kinsey, que na década de 1950 promovem essa ruptura ao desenvolver inquéritos populacionais sobre comportamento sexual na população geral, deixando assim de lado a idéia de "desvios sexuais" 1 . No Brasil, as pesquisas sobre comportamento sexual sofrem um incremento e interesse espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
30

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 22 publications
0
45
0
30
Order By: Relevance
“…Several studies have presented this cyclical characteristic of the population. 4,5 On the other hand, the refusal rate was low (2.3%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies have presented this cyclical characteristic of the population. 4,5 On the other hand, the refusal rate was low (2.3%).…”
Section: Discussionmentioning
confidence: 94%
“…5 Among the preliminary results, it was concluded that some of the individuals who had asked for sterilization through SUS in Ribeirão Preto did not obtain the procedure. c The reasons for not obtaining it might be related to giving up the idea of the operation or postponing it, consequent to counseling, or they might be related to obstacles due to failings of the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Com relação a essa temática no âmbito da enfermagem no Brasil, muitos estudos vêm sendo realizados (Pacagnella, Vieira & Rodrigues Júnior, 2008;Pimenta et al,2009) O HINT é um teste canadense, simples para ser aplicado em tempo inferior a trinta minutos por pro ssionais envolvidos com avaliação neuromotora da criança considerada de risco ou não, na idade de 3 a 12 meses. Foi criado em 1993 e revisado em 2004.…”
Section: Introductionunclassified
“…The Female Sexual Function Index, a 19-item questionnaire addressing the four clinical entities defined by the DSM-IV, that had been used in a 96 generic patient sample (both genders) indicating 40% of changes in the female sexual desire. 26 This questionnaire is currently validated for Portugal, 27 but at the time this study began only a Brazilian version existed. 28 The second available questionnaire was the Short Personal Experiences Questionnaire, which had been used in a multicentre study involving 12 countries, including Portugal.…”
mentioning
confidence: 99%